Improving Students' Motivation and Learning Outcomes Using Edmodo Learning Media Assisted with Meeting Room Media on The Circulation System Materials - Muhammad Wajdi; Nurdiyanti; Nurhasyinah Amir (IJORER : International Journal of Recent Educational Research, 2021)
The development of technology in Indonesia in the field of education is no stranger to a teacher. For this reason, a teacher is required to master technology. One of the most widely used educational technologies today is online-based learning media. Through this research, it is able to increase the teacher's insight in sorting out the suiTable learning media for use in the learning process. This type of research is classroom action research. The purpose of this study was to determine the increase in motivation and learning outcomes of students using Edmodo learning media assisted by meeting room media on the circulation system material. Classroom Action Research in its implementation uses a cycle pattern, where each cycle requires three meetings and the level of research completion depends on the extent to which the level of achievement of learning success is adjusted to the assessment standards. Each cycle in this research consists of the stages of Planning, Action, Observation / Evaluation, and Reflection activities. The results showed that the use of Edmodo learning media assisted by meeting room media can increase the motivation and learning outcomes of students in the circulation system material.